2006
DOI: 10.1007/s10164-006-0192-8
|View full text |Cite
|
Sign up to set email alerts
|

The language of lizards: interpreting the function of visual displays of the Indian rock lizard, Psammophilus dorsalis (Agamidae)

Abstract: The first step in understanding any communication system is to document signal diversity relative to the context of signalling (e.g. sex of the signaller and audience). Observation of 30 free-ranging rock lizards (Psammophilus dorsalis) on rock outcrops in southern India over a period of 18 months revealed that these lizards produce a complex array of ritualized signals involving push-ups (headbobbing), dorsal flattening, extension of the legs or gular region, and tail-raising. Push-ups were performed by both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 60 publications
4
25
0
1
Order By: Relevance
“…Rest behaviours during the courtship were almost similar to other agamid lizards (Pandav et al, 2007;Radder et al, 2006). The display act through dewlap extension/fanning by the male of Sitana cf.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Rest behaviours during the courtship were almost similar to other agamid lizards (Pandav et al, 2007;Radder et al, 2006). The display act through dewlap extension/fanning by the male of Sitana cf.…”
Section: Discussionsupporting
confidence: 65%
“…Though not unique to the species, this act is not well pronounced in other agamids found in this part of the country. Push-up displays by both the sexes have been reported in Calotes versicolor (Pandav et al, 2007) and Psammophilus dorsalis (Radder et al, 2006); however in case of S. cf. ponticeriana, this display was not observed for females.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These lizards orient themselves visually while chemoreception is poorly developed in juveniles (Ammanna, Saidapur and Shanbhag, unpublished observations). The agamid lizards (e.g., Amphibolurus muricatus, Psammophilus dorsalis, C. versicolor) are known to use vision for detection of food, predators, and communication between conspecifics (Husak, 2004;Radder et al, 2006;Shanbhag et al, 2010). Extensive studies on A. muricatus and the iguanid Sceloporus graciosus have revealed that they exhibit push-ups and guiar extensions upon encounter with unfamiliar conspecifics (Martins, 1993;Ord and Evans, 2003;Van Dyk and Evans, 2007).…”
Section: Introductionmentioning
confidence: 99%